Inovação nas rotinas de planejamento estratégico da rede de ensino de João Pessoa : um estudo de caso baseado no mapeamento de processos - Alves, Ana Paula Pereira (2024)
Planning is an essential foundation for the effective functioning of any organization, guiding the completion of tasks and the achievement of objectives. This study had the general objective of analyzing how the theory of process mapping contributes to the strategic planning process of the education network in João Pessoa, Paraíba, with specific objectives: carrying out an organizational diagnosis, identifying bottlenecks in planning routines and the proposal for an organizational planning manual based on process mapping theory. Aiming to achieve these objectives, we adopted applied research, with a qualitative descriptive and documentary approach, using a case study as a method that proposes a deep and contextualized understanding of the organizational planning processes of the João Pessoa Education Network. The research involved the municipal education network, more particularly the planning that is aimed at the Final Years, students from the 6th to the 9th year of Elementary School, with the participation of members of the Aruanda Municipal School and employees of the Directorate of Education, Management and SEDEC Training School. The procedures and techniques included document survey, semi-structured interview and process mapping. Among the tools for building Strategic Planning, diagnosis and mapping, we use the elaboration of the organization's Mission, Vision and Values concepts, SWOT Analysis, BPMN modeling, the 5W2H tool and the PDCA Cycle. As a result of the research, we propose the Manual of planning routines for the João Pessoa education network, we identify important documents that guide planning actions and govern the attributions of the subjects who put it into practice. We verified the need for specific public policies aimed at the Final Years, as well as the implementation of better working conditions for education professionals. To improve the flow of planning actions in the DEGEF organization chart, we suggest the creation of a specific department for Elementary II and two new divisions to focus on actions aimed at the Final Years. We also saw that last-minute demands greatly harm the teacher's professional practice, making it necessary to anticipate planning guidelines and simplify information to optimize practice and, consequently, student teaching and learning. Therefore, this research was relevant to improve planning processes in the João Pessoa education network, contributing to the professional practice of educators and the achievement of the institution's objectives. This study also contributed to future studies on organizational strategic planning, process mapping, teaching planning for the Final Years, improving what is already carried out in municipal schools and contributing to quality education.